Labor Market Insertion of Female Immigrants from Venezuela, 2014-2019: Accumulation of Disadvantages? - Moyano-Buitrago, María Luz (Sociedad y Economía, 2021)
Since 2014, Colombia has experienced a significant presence of individuals coming from Venezuela due to the crisis in that country. The objective of this research is to study the labor market insertion of Venezuelan women and evaluate whether they present accumulated disadvantages. Using information from the GEIH for 2014-2019, this article compares some labor indicators of Venezuelan women in Colombia versus locals and other immigrant groups. The results indicate that Venezuelan women are similarly likely to be employed compared to other women, but receive lower incomes, work longer hours, are less likely to belong to the formal sector and have more precarious working conditions. Although the time of settlement improves their labor outcomes, the gaps between Venezuelan and local women remain wide. The evidence suggests that the population analyzed experiences an accumulation of vulnerabilities, which is why it is important to approach future studies from an intersectionality approach.